Fall definitions, faller classifications and outcomes used in falls research among people with multiple sclerosis: a systematic review. Issue 6 (13th March 2022) - O'Malley, Nicola; Clifford, Amanda M.; Comber, Laura; Coote, Susan
Abstract: Purpose: To identify the definitions of a fall, faller classifications and outcomes used in prospectively-recorded falls research among people with Multiple Sclerosis (MS). Methods: A systematic review of peer-reviewed journal articles was conducted using electronic databases. Relevant data were extracted by one reviewer and verified by a second independent reviewer. Results: Twenty-six papers met the inclusion criteria. A relative degree of heterogeneity existed amongst studies for the outcomes of interest to this review. Thirteen different fall definitions were identified. Fourteen different falls outcomes were used across the included studies, with six of these reported by only one study each. Data regarding injurious falls were presented by only eight papers. The majority ( n  = 17) of papers classified individuals as a faller if they fell at least once. Conclusions: This review highlights the large variation in fall definitions, faller classifications and outcomes used in this research field. This hinders cross-comparison and pooling of data, thereby preventing researchers and clinicians from drawing conclusive findings from existing literature. The creation of an international standard for the definition of a fall, faller classification and falls outcomes would allow for transparent and coordinated falls research for people with MS, facilitating progression in this research field. Implications for rehabilitation: Falls are a common occurrence among people with Multiple Sclerosis (MS) resulting in numerous negative consequences. There is large heterogeneity in the definitions, methods and outcomes used in falls research for people with MS. This lack of standardisation prevents the accurate cross-comparison and pooling of data, impeding the identification of falls risk factors and effective falls prevention interventions for people with MS. Consequently, clinicians should interpret the outcomes of falls research for people with MS with caution, particularly when comparing studies regarding falls risk assessments and falls prevention interventions for use in clinical practice.